Gender-bender: Perceptions of College Students in Tangerang on the Portrayal of Gender Roles in Popular Media - Juan Osbert Ethan Widjaya; Deborah Nauli Simorangkir (Ultimacomm: Jurnal Ilmu Komunikasi, 2023)
Media representation defines social reality by virtue of meanings negotiated through symbols, creating symbolic boundaries that define identities, one of which is gender. Symbolic boundaries of gender have revolved around the roles of masculinity and femininity, much of which were socialized by the media. Dove Cameron’s “Breakfast” music video (2022) challenges symbolic boundaries by portraying boundary-crossing through the role reversal of men and women. Through focus group discussions with male and female participants, this study sought to evaluate the way messages of symbolic gender boundaries are portrayed, and how Indonesian young audiences respond to modern representations of gender boundaries. Data were analyzed using the Stuart Hall's Reception Analysis perspective. Results showed that Indonesian younger audiences -male and female- react positively and are receptive to the messages of gender boundary-crossing, and they actively reconstruct the symbolic boundaries of gender. The study ﬁnds that participants have progressive deﬁnitions of gender, with various aspects of their background inﬂuencing their views on gender. The symbolic boundaries of gender include characteristic traits, appearance, and sexualities. Ultimately, similar results were gleaned from both the male and female groups.